Improving the performance of electrical duty-cycle division multiplexing with optimum signal level spacing - Mahdiraji, G.A.; Abas, A.F. (Optics Communications, 2012)
Performance optimization of 3 x 10 Gbps conventional electrical-duty-cycle division multiplexing (C-E-DCDM) technique is investigated. It is shown that controlling signal level spacing can optimize its performance. Two level spacing optimization techniques, one in electrical domain and another in optical domain are examined. In general, performance of the C-E-DCDM is improved significantly using both approaches. The results show by optimization, an improvement of around 5.5 dB can be achieved for the C-E-DCDM in terms of receiver sensitivity and optical signal-to-noise ratio using both electrical and optical methods. However, chromatic dispersion tolerance in one of the optimization approaches is degraded by around 34 ps/nm for negative dispersion, while the positive dispersion tolerance improved compared to the C-E-DCDM. (C) 2011 Elsevier B.V. All rights reserved.